Beclin 1 Influences Cisplatin-Induced Apoptosis in Cervical Cancer CaSki Cells by Mitochondrial Dependent Pathway. Issue 7 (1st September 2012) - Sun, Yang; Liu, Jia-hua; Jin, Long; Pan, Ling; Sui, Yu-xia; Yang, Yin; Shi, Hong
Abstract : Purpose: To investigate the role of Beclin 1 expression on the cisplatin-induced apoptosis in cervical cancer CaSki cells and to explore the potential mechanism underlying this effect. Materials and Methods: After overexpression or partial silencing of Beclin 1 in cervical cancer CaSki cells, the transfected group and the control group were treated with cisplatin for 24 hours. The percentage of apoptotic cells were assessed by flow cytometry. The mitochondrial membrane potential and activities of caspase-8/9/3 were detected by JC-1 fluorescence staining and colorimetry. The expression of cytochrome c was measured using a Western blot. The messenger RNA expression of Bax and Bcl-2 were detected by real-time quantitative reverse transcription polymerase chain reaction. Results: Expression of Beclin 1 protein was up-regulated in overexpressed transfectants of CaSki cells. After treatment with cisplatin, the Beclin 1 overexpression group led to the decrease of mitochondrial membrane potential and increase of activities of caspase-9 and caspase-3, and showed a greater increase in apoptosis than did the nontransfected group. Furthermore, Beclin 1 overexpression resulted in increased cytoplasmic cytochrome c and Bax expression and decreased mitochondrial cytochrome c and Bcl-2 expression. Conclusion: Overexpression of Beclin 1 in CaSki cells may influence cisplatin-induced apoptosis by mitochondrial dependent pathway.